Design and simulation of Piezoresistive tactile sensor - Nahmar Harun (Universiti Malaysia Perlis, 2008)
Piezoresistive tactile sensor is use to measure contact force and to characterize surface roughtness of the object. The main application of piezoresistive tactile sensor is in robotic dexterous manipulations tasks. This device is still under research. Much research has focused on improving sensor precision, reliability, sensitivity and ease manufacturing process. However, this device has commercialization potential in the future when the use of robot becomes more common.This project requires in depth knowledge in MEMS (MicroElectroMechanical Systems). The knowledge of fabrication process, simulation software and piezoresistive effect is important. The tactile sensor must having linear output and good sensitivity and can detect small force. The result of simulation will be discusses and compare with theoretical result.